Cardiovascular disease and brain health: Focus on white matter hyperintensities. (June 2018) - Moroni, Francesco; Ammirati, Enrico; Rocca, Maria A.; Filippi, Massimo; Magnoni, Marco; Camici, Paolo G.
Abstract: Diseases affecting the brain contribute to a substantial proportion of morbidity and mortality in the general population. Conditions such as stroke, dementia and cognitive impairment have a prominent impact on global public health. Despite the heterogeneous clinical manifestations of these conditions and their diverse prognostic implications, current evidence supports a role for cardiovascular disease as a common pathophysiological ground. Brain white matter hyperintensities (WMH) are patchy white matter signal hyperintensity on T2-weighted magnetic resonance imaging sequences commonly found in elderly individuals. WMH appear to have a vascular pathogenesis and have been shown to confer an increased risk of stroke and cognitive decline. Indeed, they were proposed as a marker for central nervous system frailty. Cardiovascular diseases seem to play a key role in the etiology of WMH. Carotid atherosclerosis and atrial fibrillation were shown to be associated with higher WMH burden, while adequate blood pressure control has been reported reducing WMH progression. Aim of the present work is to review the available evidence linking WMH to cardiovascular disease, highlighting the complex interplay between cerebral and cardiovascular health.